Age-related differences in auditory spatial processing revealed by acoustic change complex - Wang, Xing; Nie, Shuai; Wen, Yining; Zhao, Zihui; Li, Jiaying; Wang, Ningyu; Zhang, Juan (Frontiers in Human Neuroscience, 2024)
Objectives: The auditory spatial processing abilities mature throughout childhood and degenerate in older adults. This study aimed to compare the differences in onset cortical auditory evoked potentials (CAEPs) and location-evoked acoustic change complex (ACC) responses among children, adults, and the elderly and to investigate the impact of aging and development on ACC responses. Design: One hundred and seventeen people were recruited in the study, including 57 typically-developed children, 30 adults, and 30 elderlies. The onset-CAEP evoked by white noise and ACC by sequential changes in azimuths were recorded. Latencies and amplitudes as a function of azimuths were analyzed using the analysis of variance, Pearson correlation analysis, and multiple linear regression model. Results: The ACC N1’-P2’ amplitudes and latencies in adults, P1’-N1’ amplitudes in children, and N1’ amplitudes and latencies in the elderly were correlated with angles of shifts. The N1’-P2’ and P2’ amplitudes decreased in the elderly compared to adults. In Children, the ACC P1’-N1’ responses gradually differentiated into the P1’-N1’-P2’ complex. Multiple regression analysis showed that N1’-P2’ amplitudes (R2=0.33) and P2’ latencies (R2=0.18) were the two most variable predictors in adults, while in the elderly, N1’ latencies (R2=0.26) explained most variances. Although the amplitudes of onset-CAEP differed at some angles, it could not predict angle changes as effectively as ACC responses. Conclusions: The location-evoked ACC responses varied among children, adults, and the elderly. The N1’-P2’ amplitudes and P2’ latencies in adults and N1’ latencies in the elderly explained most variances of changes in spatial position. The differentiation of the N1’ waveform was observed in children. Further research should be conducted across all age groups, along with behavioral assessments, to confirm the relationship between aging and immaturity in objective ACC responses and poorer subjective spatial performance.